How Do Omega-3 and Omega-6 Fatty Acids Influence the Development of Common Acne? - Rogalski, Paweł; Pomianek, Malwina; Makara, Katarzyna; Celarek, Victor; Makara, Karolina (Journal of Education, Health and Sport, 2024)
Introduction: Acne is one of the most common skin problems affecting people worldwide, especially young individuals. Despite many years of research into the etiology of acne, its exact causes remain a subject of debate. In recent years, increasing scientific interest has focused on the role of diet in shaping skin health, including the influence of omega-3 and omega-6 fatty acids on the severity of acne symptoms. Objective: The aim of this study is to review the scientific literature regarding the relationship between a diet rich in omega-3 and omega-6 fatty acids and the reduction of acne. We will analyze available scientific evidence and attempt to determine whether dietary changes to increase the intake of these fatty acids may have a beneficial impact on skin condition and reducing the severity of acne symptoms. Results: Several studies suggest that a diet rich in omega-3 fatty acids, especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and relatively low in omega-6 fatty acids may be associated with a reduction in acne severity. Some clinical studies have shown that supplementation with omega-3 fatty acids can lead to a reduction in the number of comedones and inflammatory skin lesions in acne patients. Conclusions: Our literature review suggests that a diet rich in omega-3 fatty acids and lower in omega-6 fatty acids may be beneficial for individuals struggling with acne. However, further clinical research is needed to confirm these observations and better understand the mechanisms of action of fatty acids on skin health. In the meantime, a balanced diet rich in omega-3-containing foods such as fatty fish, nuts, and seeds is recommended as a potential adjunct to acne treatment.